Transforming South Asia imperatives for action - Bhatia, Rajiv K.; Singh, Swaran 1961-; Marwah, Reena 1960- (KW Publishers Indian Council of World Affairs, 2014)
Papers presented at the Third Asian Relations Conference, held at New Delhi in March 2012 organized by Indian Council of World Affairs, New Delhi in collaboration with Association of Asia Scholars